Moscow and Napoleon in the Novel “Eugene Onegin”: Correlation of Meanings - Alexander V. Gulin (Два века русской классики)
The article examines the “Napoleonic” stanza XXXVII from the Seventh Chapter of the novel “Eugene Onegin” in the context of poetics, problematics, and the spiritual ideal of the work. Pushkin’s analogy of the figurative pairs “Napoleon — Moscow” and “Onegin — Tatiana” appears the most important and meaningful. The research demonstrates that mentioning the only historical person in the novel acting in a concrete historical situation is extraordinary for the artistic system of “Eugene Onegin” and largely organizes Pushkin’s hierarchy of meanings. The article reveals the place of the lyrical digression from the novel among Pushkin’s numerous insights into the mystery of Napoleon’s personality. The involvement of historical materials from 1812 helps to disclose the comprehensive poetic formula of “generous fire” from earlier Pushkin’s works. The fire of Moscow and Tatiana’s sacrifice are seen as the realization and victory of Christian life values. Pushkin’s description of the historical event and the final explanation of Onegin and Tatiana reveals a profound unity of the national spiritual code, rejecting the Napoleonic principle of life and eternally triumphant over the world turmoil.